Association between irrigation thresholds and promotion of soil organic carbon decomposition in sandy soil - Jean-Pascal Matteau (Nature Portfolio, 2021)
Abstract Soil organic carbon (SOC) has a significant effect on the carbon cycle, playing a vital role in environmental services and crop production. Increasing SOC stock is identified as an effective way to improve carbon dioxide sequestration, soil health, and plant productivity. Knowing soil water is one of the primary SOC decomposition driver, periods in the crops growth stages with increased water movement might influence the SOC dynamics. Here, we evaluate the temporal effect of four precision irrigation thresholds ( $$-15$$ - 15 , $$-30$$ - 30 , $$-45$$ - 45 , and $$-60$$ - 60 kPa) in potato crop on SOC dynamics using the Partial Least Square algorithm and the Tea Bag Index in a sandy soil under potato production. The difference of SOC decomposition rate between the precision irrigation thresholds is developed in the second quarter of the growing season, between 38 and 53 days after planting. This critical period occurred in a stage of strong vegetative growth and rapid irrigation cycles. The precision irrigation threshold affected the decomposition rate of SOC. A faster decomposition of labile organic carbon was promoted by water excess ( $$-15$$ - 15 kPa). The dryer ( $$-30$$ - 30 , $$-45$$ - 45 , and $$-60$$ - 60 kPa) precision irrigation thresholds did not show any differences. The advancement of this knowledge may promote soil health conservation and carbon sequestration in agricultural soil.